The bookshop of second chances : [large type] a novel - Fraser, Jackie, 1972- (Thorndike Press large print romance, 2021)
"Thea Mottram is having a bad month. She's been let go from her office job with no notice--and to make matters even worse, her husband of nearly twenty years has decided to leave her for one of her friends. Bewildered and completely lost, Thea doesn't know what to do. But when she learns that a distant great uncle in Scotland has passed away, leaving her his home and a hefty antique book collection, she decides to leave Sussex for a few weeks. Escaping to a small coastal town where no one knows her seems to be exactly what she needs. Almost instantly, Thea becomes enamored with the quaint cottage, comforted by its cozy rooms and lovely but neglected garden. The locals in nearby Baldochrie are just as warm, quirky, and inviting. The only person she can't seem to win over is bookshop owner Edward Maltravers, to whom she hopes to sell her uncle's book collection. His gruff attitude--fueled by an infamous, long-standing feud with his brother, a local lord--tests Thea's patience. But bickering with Edward proves oddly refreshing and exciting, leading Thea to develop feelings she hasn't experienced in a long time. As she follows a thrilling yet terrifying impulse to stay in Scotland indefinitely, Thea realizes that her new life may quickly become just as complicated as the one she was running from."--